Prototype of IOT Based Traffic Light Control System with Infrared Sensor Based on Vehicle Density - Dina Maizana; Ronal Kristian Manurung; Moranain Mungkin (INFOKUM, 2026)
Traffic congestion is one of the main challenges in densely populated urban areas. Conventional traffic light systems generally work based on fixed times without considering real conditions in the field. This study aims to design a prototype of an automatic traffic light control system that is able to adjust the turn-on time based on vehicle density. The system uses infrared light-based sensors to detect the number of vehicles on each Line in real-time. The detection data is processed by the ESP32 nodemcu to determine which Line gets the green light first. The system is designed to work alternately and dynamically so that all Lines get a chance, but still prioritizes the most congested Line. Test results show that this system is able to reduce vehicle queues and improve traffic flow